Cholera Presenting With Hyperkalemia, Rhabdomyolysis, and Acute Renal Failure. Issue 11 (30th November 2020) - Grubb, Seth M; Riddle, Mark
ABSTRACT: Cholera is a well known cause of significant disease, particularly in resource-poor nations, but it is very rare in developed countries. The morbidity and mortality of cholera is resultant from large-volume diarrhea, hypovolemia, and electrolyte derangement. In the following case, a 60-year-old man with no recent travel history presented to the emergency department with muscle cramping, abdominal pain, and gastrointestinal distress. It was later confirmed that he was suffering from cholera. On presentation, he was hyperkalemic with ECG changes and soon went into a hypovolemic shock. After a complicated hospital course, he fortunately made a complete recovery. This case demonstrates that common complaints may result in uncommon diagnoses. It is important to pay attention to the clinical situation and intervene accordingly.